2004
DOI: 10.1111/j.0014-3820.2004.tb00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Linkage Disequilibrium Generate Heterozygosity-Fitness Correlations in Great Reed Warblers?

Abstract: Abstract. Heterozygosity-fitness correlations (HFCs) at noncoding genetic markers are commonly assumed to reflect fitness effects of heterozygosity at genomewide distributed genes in partially inbred populations. However, in populations with much linkage disequilibrium (LD), HFCs may arise also as a consequence of selection on fitness loci in the local chromosomal vicinity of the markers. Recent data suggest that relatively high levels of LD may prevail in many ecological situations. Consequently, LD may be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(169 citation statements)
references
References 108 publications
(159 reference statements)
7
159
3
Order By: Relevance
“…Earlier genetic studies have shown that the great reed warbler has a very variable MHC (Westerdahl et al 1999(Westerdahl et al , 2004b and that it is advantageous to be heterozygous at MHC class I loci, because such individuals tend to have higher survival (Hansson et al 2004). Specifically, we found that one MHC class I allele (B4b) varied significantly in frequency between years among cohorts in the breeding population (Westerdahl et al 2004a).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Earlier genetic studies have shown that the great reed warbler has a very variable MHC (Westerdahl et al 1999(Westerdahl et al , 2004b and that it is advantageous to be heterozygous at MHC class I loci, because such individuals tend to have higher survival (Hansson et al 2004). Specifically, we found that one MHC class I allele (B4b) varied significantly in frequency between years among cohorts in the breeding population (Westerdahl et al 2004a).…”
Section: Introductionmentioning
confidence: 52%
“…(c) Screening of microsatellite variation To obtain an average estimate of the heterozygosity in the entire great reed warbler genome, 340 individuals were typed for allelic variation at 18 microsatellite loci: Aar2-5, Aar8 ; Ppi2 (Martinez et al 1999); Ase7, Ase9, Ase11, Ase18, Ase34, Ase42, Ase44, Ase58, Ase60 (Richardson et al 2000); Ase15 (D. S. Richardson, unpublished work; see Hansson et al 2004); Hru5 (Primmer et al 1996); and Sjr4 (D. B. McDonalds & W. K. Potts, unpublished work; see Hansson et al 2000). Primer sequences and amplification conditions are given in Hansson et al (2000Hansson et al ( , 2004.…”
Section: (A) Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on MHC variation in natural populations have identified associations of specific alleles to resistant or susceptible individuals (Meyer-Lucht and Sommer 2005;Schad et al 2005), heterozygote advantage (Hansson et al 2004), and combinations of heterozygote advantage and frequency-dependent selection (Froeschke and Sommer 2005). In three-spined sticklebacks (Gasterosteus aculeatus), intermediate rather than maximal allele numbers were associated with minimal parasite load in individual fish (Wegner et al 2003a,b), suggesting that other forms of selection are also acting on these loci.…”
Section: Parasite Communitymentioning
confidence: 99%
“…These peptides are presented to the T-cells, and this interaction elicits an immune response. The range of peptides an individual can successfully present to the immune system is predicted to be associated to an individual's immunocompetence, and hence, to its parasite resistance (Nei and Hughes 1991).Balancing selection appears to be important in maintaining high variability observed at many MHC genes (Hedrick 1999a), and many recent studies detected associations between parasite resistance and MHC heterozygosity (Penn et al 2002) or particular MHC alleles (Hansson et al 2004;Harf and Sommer 2005;Meyer-Lucht and Sommer 2005;Schad et al 2005). Nevertheless, several enigmatic questions still remain.…”
mentioning
confidence: 99%